Corporate Social Responsibility: A Business Solution for Sustainable and Inclusive Development - Singh, Raj Kumar (Prabandhan: Indian Journal of Management, 2013)
The two significant events of the year 1970 - one, Milton Friedman’s pronouncement that ’the only social responsibility of business is to make profits’, second, back home J.R.D. Tata passed instructions to all Tata Group companies to include a clause on ’stakeholders management’ in their articles of association. It took 43 years to transform stakeholders’ philosophy into reality, with the enactment of the Companies Act, 2013, which for the first time incorporated the significant clause of corporate social responsibility and has made it mandatory for companies to spend 2% of their profits after tax on CSR activities. The CSR concept is a trade-off between capitalistic and socialistic ideology. In this research paper, a modest attempt has been made to understand and analyze the concept of sustainable development in the emerging global economic scenario, evaluate the inclusive development in the backdrop of budgetary allocation to the social sector, and study the implications of corporate social responsibility for sustainable and inclusive development. Finally, it has been concluded that CSR initiatives will help businesses to become economically viable and equitable, socially responsible, and environmentally sustainable.